A cross-sectional study of thyroid dysfunction in patients of chronic kidney disease in Goa medical college - Managooli, Mahesh; Nadekar, Prashanth B.; Pauskar, Mahendra Manoj (International Journal of Research in Medical Sciences, 2024)
Background: Thyroid hormones are essential for regulating metabolism, development, protein synthesis, and other hormone functions. CKD has been linked to changes in the pituitary-thyroid axis and peripheral thyroid hormone metabolism. Methods: A cross-sectional study was conducted in 100 subjects from September 2019 to September 2021 in the department of medicine, Goa Medical College, a tertiary care hospital in Goa. Results: Most of the CKD patients in study population are in the Age group of 41-70 years. 70% were male. 54% patients were diabetic and 46% patients were non diabetic, majority of them 87% patients were hypertensive, majority of them were DM and HTN With 88% and few patients belonged to other diseases. 8% patients with high TSH level, 6% with low TSH level, 86% with normal TSH level. TT4 levels were low in 28% patients and normal in 72% patients, TT3 levels were high in 3% patients, low in 60% and normal in 37% patients. FT4 levels were high in 5% patients and low in 7%, normal in 88% patients. FT3 levels were high in 1% patients, low in 49%, normal in 50% patients. 55% patients belong to euthyroid state and 7% patients belongs to hypothyroid state and 36% patients belong to sick euthyroid state and 2% belongs to subclinical thyrotoxicosis. Conclusions: Most of the participants in this study were euthyroid. The most common thyroid hormone derangement was low T3 values (non-thyroidal illness). The prevalence of hyperthyroidism in this study was 2% and hypothyroidism 7%.